1992
DOI: 10.1093/rfs/5.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Stock Prices and Volume

Abstract: We undertake a comprehensive investigation of price and volume co-movement using daily New York Stock Exchange data from 1928 to 1987. We adjust the data to take into account well-known calendar effects and long-run trends. To describe the process, we use a seminonparametric estimate of the joint density of current price change and volume conditional on past price changes and volume. Six empirical regularities are found: 1) highly persistent price volatility, 2) positive correlation between current price chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
565
3
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,161 publications
(638 citation statements)
references
References 55 publications
68
565
3
2
Order By: Relevance
“…Mei et al 12 found that trading caused by investors' speculative motives could explain a significant fraction of the price difference between the dual-class shares. Gallant et al 13 investigated the price and volume co-movement using daily data from 1928 to 1987 for the New York stock exchange and found positive correlation between conditional volatility and volume. Griffin et al 14 investigated the dynamic relation between market-wide trading activity and returns in 46 markets and reported a strong positive relationship between turnover and past returns.…”
Section: Volume and Stock Price Movementsmentioning
confidence: 99%
“…Mei et al 12 found that trading caused by investors' speculative motives could explain a significant fraction of the price difference between the dual-class shares. Gallant et al 13 investigated the price and volume co-movement using daily data from 1928 to 1987 for the New York stock exchange and found positive correlation between conditional volatility and volume. Griffin et al 14 investigated the dynamic relation between market-wide trading activity and returns in 46 markets and reported a strong positive relationship between turnover and past returns.…”
Section: Volume and Stock Price Movementsmentioning
confidence: 99%
“…The performance of the MCL estimator is further illustrated by fitting the model to the seasonally adjusted (Gallant et al, 1992) S & P 500 returns. JPR and Danielsson (1994b) has already utilized a subset of the data (2/1/80-30/12/87, ¹"2,022 observations) to fit the basic SV model.…”
Section: S and P500 Return Seriesmentioning
confidence: 99%
“…For ease of reference the results of the basic SV are reproduced in the upper panel. The Gallant et al (1992). The sample length is ¹"2022 observations.…”
Section: Extensions Of the Basic Sv Model (I): Heavy ¹Ailsmentioning
confidence: 99%
“…Proposition 5 has been empirically documented in several studies, see, for instance, Gallant, Rossi, and Tauchen (1992) or Karpoff (1987) for earlier references. Chordia, Roll, and Subrahmanyam (2002) and Chan and Fong (2000) additionally highlight the effect of the order imbalance on price variability, providing evidence for both Propositions 4 and 5.…”
Section: Proposition 5 (Price Variability and Volume)mentioning
confidence: 92%
“…Proposition 4 order imbalance ր average absolute price change ր Chordia, Roll, and Subrahmanyam (2002), Chan and Fong (2000) Proposition 5 volume ր average absolute price change ր Chordia, Roll, and Subrahmanyam (2002), Chan and Fong (2000), Gallant, Rossi, and Tauchen (1992) Proposition 7 entry rate ր average volume ր average order imbalance ր average price changes ր duration ց causes for changes in entry rate: index inclusion, international market opening financial deregulation, cross-listing Propositions 8 & 9 information quality ր price impact ր average volume ր average order imbalance ր average price changes ր duration ց , Roll, and Subrahmanyam (2008), causes for changes in information quality: new disclosure rules, changes in analyst coverage, changes in information technology, changes in ownership structure (hedge funds rather than mutual funds), development of a new analysis tool, improvements in analysts' earnings forecasts Proposition 10 informed trading ր average volume ց duration ր (numerically) price changes ր causes for changes in the proportion of informed trading: changes in ownership structure (hedge funds rather than retail), market changes that trigger more retail participation or day trading …”
Section: Claim (Ii)mentioning
confidence: 99%